EFL teachers’ commitment to professional ethics and their emotional intelligence: A relationship study - Hamid Ashraf; Mansooreh Hosseinnia; Javad GH. Domsky (Cogent Education, 2017)
Emotional intelligence is the capability to realize, to create, to comprehend emotions and sentimental knowledge, and to reflectively control emotions and to improve emotional and mental growth. The purpose of this study is to examine the relationship between EFL teachers’ commitment to professional ethics and their emotional intelligence. To collect the data, 357 EFL teachers—selected based on Krejcie and Morgan’s table of sample size (1970)—participated in this research. Validated and reliable scales of assessing emotional intelligence and professional ethics were utilized. In this study, descriptive statistics as well as inferential statistics of each principle was performed. Also, for estimating the results, Pearson Product-moment Correlation analysis was utilized. According to the results, there is a significant positive relationship between 9 and 10 the professional ethics principles especially dual relationship with students principle and emotional intelligence. Since there is an increase in commitment of teachers to professional ethics, their emotional intelligence has increased too.